Political Meritocracy as Eastern Alternative to the Western Public Administration Traditions in the 21st Century - V. S. Gerasimov (Vestnik MGIMO-Universiteta)
The article discusses political meritocracy phenomenon. The author examines political and economic backgrounds of the meritocracy concept occurrence within the political science discourse as well as distinctive features of that process. Special emphasis is put on economic situation of the early 1980s when the governments of various states were challenged with the necessity of overcoming the consequences of the global economic crisis of the preceding decade. The author focuses on similarities and distinctions within the policies which have been implemented by the various states at that period paying special attention to the form of the political regime in those countries. Also the author draws attention to the discussion on "Asian values" which played significant role in the political meritocracy coming-to-be process within Asian region. The article analyses origin and dissemination of the meritocratic approaches among public administration practices of some countries within Asian region (eg. China and Singapore). The author reveals main theoretical grounds of the political meritocracy and researches culturological backgrounds of those theoretical grounds. Specifically, he studies the significance of the Confucianism moral-ethic doctrine regarding theory and practice of meritocracy. Additionally the author traces the displays of the meritocratic principles within the views of the various representatives of the western political theory among which both classic (Plato, J.St. Mill) and contemporary (Brennan J., Caplan B.) thinkers are represented. In conclusion the author analyses the opportunities of the meritocratic theory and practice implementation in Russian reality. He compares Russia, China and Singapore via the list of criteria of political and economic importance, reveals similarities and distinctions in the political past and present of those states, estimates the significance of some culturological factors regarding the evolution of those states and formulates his conclusion on the prospective of meritocracy in Russia.